RESEARCH OF THE EDUCATIONAL VALUE OF MORAL VALUES OF THE YOUNG GENERATION USING THE MEANS OF ETHNOLOGY - Лебідь, В.П.; Харченко, І.М. (Modern engineering and innovative technologies, 2023)
The article presents the directions of psychological anthropology, which considers the specifics of perception, cognition, thinking, moral values ​​and their education in students. Pedagogical substantiation of the need to educate moral values ​​on a nati